Effect of combined ß-alanine and sodiumbicarbonate supplementation on cycling performance - Bellinger, P. M.; Howe, S. T.; Shing, C. M.; Fell, J. W. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The purpose of this study was to investigate the effects of 28 d of ß-alanine supplementation on 4-min cycling time trial performance and to determine whether there was an additive effect of combined ß-alanine and sodium bicarbonate (NaHCO3) supplementation on high-intensity cycling performance.